Pendampingan perancangan ruang pamer museum dr.AK.Gani pada pameran bersama Museum Negeri Sumatera Selatan - Shinta Puspasari (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2021)
A successful exhibition cannot be separated from the proper arrangement of the exhibition space. A good exhibition space arrangement will generate interest from exhibition visitors. Moreover, what if the exhibition is a museum exhibition. The arrangement of museum exhibitions requires a more complex arrangement. South Sumatra Province held a joint exhibition which various state museums throughout South Sumatra attended. Because various museums attend it, a good exhibition space arrangement is needed to present an optimal exhibition space so that it is attractive to visitors and is not inferior to other museums in the exhibition. Therefore, this service aims to assist dr.AK.Gani Museum as a partner to organize its exhibition space to make it more optimal. The community service activities offered at this activity are assistance in designing informative brochures and showing off collections. Exhibition activities went well and safely following health protocols during the COVID-19 pandemic, attended by various students and the general public. The activity method includes focus group discussions, exhibition room design, and effective exhibition space design implementation to produce the dr.AK.Gani Museum exhibition design has been implemented at the 2020 Joint Exhibition at the South Sumatra State Museum